Cone evolution on VUV laser ablated polymers - Zakaria, Rozalina; Dyer, Peter E. (Springer, 2010)
We report on conical microstructures formed on polycarbonate and polyallyl di-glycol carbonate (CR39) ablated using 157-nm F2 laser radiation. These are distinguished by having smooth, straight walls and, for CR39, sharp tips, together with interference and diffraction fringes around their base. Etch-rate modelling of a non-planar surface and diffraction-modulated fluence is used to explore how cones may evolve, and an estimate is made of thermal loading on microcones.